Effectiveness of Direct Observation of Procedural Skills (DOPS) for Improving the Mini-Implant Insertion Procedural Skills of Postgraduate Orthodontic Trainees - Muhammad Azeem, Ambreen Usmani, Abid Ashar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: College of Physicians & Surgeons Pakistan (CPSP) has recently introduced different WBA tools in various specialties, but Directly Observed Procedural Skills (DOPS) is still required to be implemented in orthodontics which will improve learning and skills of the learner. Aim: To determine the effect of applying DOPS for improving the mini-implant insertion procedural skills of postgraduate orthodontic trainees. Methodology: This quantitative, quasi-experimental study was conducted at orthodontic department of de’Montmorency College of Dentistry (DCD), Lahore, from 1st July 2021 to 1st November 2021. Twenty trainees were selected and assessed over a period of 3 months which included 3 DOPS encounters with one-month interval between each encounter for mini-implant insertion. The trainees were assigned to faculty for each DOPS encounter by randomization. At the end, the trainees’ and the faculty’ perception regarding feasibility and acceptability of DOPS were obtained by means of structured questionnaire. The pre-DOPS and post-DOPS mean scores of all the trainees were compared using paired t-test. Results: Mean scores of all the orthodontic trainees significantly improved in the post-DOPS as compared to the pre-DOPS encounter, which may be linked to the feedback of 2nd DOPS session. As per results, the DOPS was perceived to be acceptable and feasible to both the faculty and trainees. Conclusion: DOPS is an effective tool for assessing and improving the mini-implant insertion procedural skills of postgraduate orthodontic trainees.